Effect of obesity over dental, periodontal and bone tissue structures during induced tooth movement in rats: microtomographic and histological analyses - Reis, Karla Orfelina Carpio Horta dos (2019)
To evaluate the effect of obesity over induced tooth movement in Wistar rats, by means of computerized micro-tomography and histological analyzes. Forty rats of approximately 125 g were randomly divided in two groups of 20 animals each, the non-obese and the non-obese groups. The left side of the maxillas of all animal received induced tooth movement (ITM = WM, with movement) for each experimental period, i.e. 7 or 14 days (OWM7, OWM14, NOWM7 and NOWM14 groups). The untreated right hemi-maxilla groups (O7, O14, NO7, NO14 groups) were also accessed. Obesity was induced by supplying a high-fat diet for eight weeks. ITM aimed the mesial movement of the left maxillary first molar using a nickel-titanium closed coil spring. After euthanasia, forty hemi-maxillas were submitted to chemical and biological processing in order to prepare the samples for microtomography examination. Also, forty hemi-maxillas were analyzed histological analyses. The number of cementoclast and osteoclasts were analyzed through staining of the enzyme tartrate-resistant acid phosphatase. Also, presence or absent of focal hyalinization (FH), frontal bone resorption (FBR) and root resorption (RR) that included active root resorption and repaired root resorption at cementum (ARRC and RRRC, respectively) and at dentin level (ARRD and RRRD, respectively), and at cervical and medial thirds of the mesial and disto-buccal roots were evaluated in sections stained with Hematoxylin-Eosin. Data was submitted to appropriate statistical analysis using the programs Graph Pad Prism 5.0 and Stata13, with a significance level of 5%. Different animal weights between groups were reported since week one (p=0.002 and p≤0.001). Obese animals showed higher rates of ITM after 7 days than non-obese animals (p=0.081). This difference became more evident after 14 days (p≤0.001). Bone surface density at compression site showed reduced values in obese animals submitted to ITM of 7 (p=0.027) and 14 days (p=0.050). After 7 days of ITM, obese animals presented a reduced number of trabecula (p=0.002), increased trabecular separation (p≤0.001) and higher total porosity (p=0.027) at compression site. However, after 14 days, trabecular number, trabecular separation, and porosity, and after 7 and 14 days, bone volume, percentage of bone volume, disto-buccal root volume and angular measurements were similar between obese and non-obese animals (p>0.05). Higher quantity of osteoclast were observed after 7 days of ITM in obese animals. Obese animals also presented decreased quantity of osteoclast after 14 days of ITM when compared to 7 days. Low frequencies of FH was observed in obese and non-obese animals after 7 days of ITM. The highest frequency of FBR was found in obese animals submitted to ITM of 7 days followed by non-obese animals at the same period. This groups presented low frequencies of FBR after 14 days of ITM. Medium and low frequencies of active root resorptions at cementum and dentin respectively were observed in obese animals submitted to 7 days of ITM while low frequencies was presented by non-obese animals. High frequency of RRRD was observed in mesial root and medium frequency at distobuccal root of obese animals submitted to 14 days of ITM, while non-obese presented low frequencies. Conclusion: Obese animals showed significantly higher rates of molar movement and different responses in morphological surrounding bone and periodontum to induced tooth movement.